Social identity theory and intergroup attributions - Finchilescu, G; Finchilescu, Gillian (1991)
﻿ The central proposition of this thesis is that intergroup attributions and explanations, like any other intergroup behaviour, are affected by the perceived relations between the groups. Social Identity Theory (SIT) was adopted as the theoretical framework within which to investigate intergroup relations. According to this theory, intergroup behaviour is affected by the relative status the groups bear to each other, together with the perceived legitimacy and stability of this status hierarchy. The thesis proposes two amendments to the theory. It is argued that perceived legitimacy and perceived stability have different effects on intergroup behaviour and hence can not be subsumed under the general category of "insecure comparisons". It is also suggested that intragroup variability exists in these perceptions. A study was conducted which confirmed these propositions, and predictions emerging from SIT concerning the effect of these perceptions on intergroup behaviour and attitudes received considerable support. In examining the effect of the intergroup perception factors on bias in intergroup attributions, the thesis focuses on two types of groups: race and gender. Three types of attribution were considered in different studies: explanations of intergroup inequality, attributions of blame for rape or robbery and attributions for individual group members' actions and outcomes. The results indicate that the relative status of the groups, together with the perceptions of the legitimacy of this status hierarchy influence the first two - the explanations for inequality and the attributions of blame made to the victim and perpetrator of crimes. In general, it appears that the 'prise de conscience' of the illegitimacy of the intergroup situation is the motivating force in rejecting the domination of the high status group over the low status group, by members of both the high and low status groups. However, the third type of attributions, the intergroup explanations made for individual group members' actions and outcomes were not in general affected by these factors. It was suggested that either the intergroup aspect of these vignettes lacked the salience to elicit an intergroup response, or that the actors in the vignettes were treated as atypical of the groups.